2009
DOI: 10.1128/cvi.00378-08
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Reference Values of CD4 and CD8 Lymphocyte Subsets in Healthy Nigerian Adults

Abstract: A total of 2,570 apparently healthy human immunodeficiency virus-negative adults from the six geopolitical zones in the country were enrolled in our study in 2006. The samples were assayed using the Cyflow technique. Data were analyzed using the Statistical Package for Social Scientists (SPSS). The majority (64%) of the participants had CD4 counts within the range of 501 to 1,000 cells/l. The reference range for CD4 was 365 to 1,571 cells/l, while the reference range for CD8 was 145 to 884 cells/l.In Nigeria, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
41
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 9 publications
26
41
6
Order By: Relevance
“…Sex influences on lymphocyte subset constitution have also been addressed in various ethnic groups (5,9,10,15,17,18). Our study also has a higher absolute count and percentage of CD3 ϩ T cells in females compared with males, while the absolute count and percentage of CD56 ϩ NK cells are higher in males (P Ͻ 0.05).…”
Section: Discussionsupporting
confidence: 49%
“…Sex influences on lymphocyte subset constitution have also been addressed in various ethnic groups (5,9,10,15,17,18). Our study also has a higher absolute count and percentage of CD3 ϩ T cells in females compared with males, while the absolute count and percentage of CD56 ϩ NK cells are higher in males (P Ͻ 0.05).…”
Section: Discussionsupporting
confidence: 49%
“…The CD4 + count level at time of diagnosis was used to provide an indication of the time delay between HIV infection and diagnosis among Nigerians as a function of normal CD4 + decay per calendar year in drug naïve individuals. The normal reference values of CD4 + counts in healthy Nigerians have been established to range from 365-1571 cells/L [18]. This reference value is supported by another study of healthy Nigerians that showed the specific mean reference CD4 + among men to be 717 cells/L and 869 cells/L among non-pregnant females [19].…”
Section: Time Period After Infectionsupporting
confidence: 51%
“…This is consistent with the NRVs [18], and in agreement with reports from previous studies [5,21].Specifically, among different age groups we recorded higher CD4 T lymphocyte values than the NRVs in this study. This is also consistent with Adoga et al, [21], who reported higher than the NRVs.…”
Section: Discussionsupporting
confidence: 83%
“…However, it is noteworthy that enrollees for the NRV study were defined as apparently healthy persons based only on their HIV negative status [18]. In this study, we estimated CD4 T lymphocyte cell values among healthy community dwellers who tested negative for HBV, HCV and HEV in Ibadan, and compared with the NRVs.…”
Section: Discussionmentioning
confidence: 99%